Effect of seawalls on tsunami evacuation departure in the 2011 Great East Japan Earthquake. Issue 6 (17th November 2018) - Troncoso Parady, Giancarlos; Tran, Bryan; Gilmour, Stuart
Abstract : Objective: To quantitatively evaluate the effect of seawalls on tsunami evacuation departure. Methods: A mixed-effect Cox proportional-hazards regression model was applied to evacuation behavioural data obtained from a probability survey of survivors of the 2011 Great East Japan Earthquake and Tsunami in Iwate and Miyagi prefectures. Findings: Presence of a seawall higher than the forecast tsunami height at any given time reduces the likelihood of prompt evacuation by 30%. Findings suggest the existence of a false sense of security among residents deriving from the presence of seawalls. Conclusion: Prompt evacuation is a key factor affecting survival. The effect of seawalls on evacuation decisions is an important policy consideration. More work is needed in disaster preparedness education and in the way tsunami warnings are given, taking into consideration the risk of forecast error. Priority should be given to promoting prompt evacuation and educating residents as to the uncertainty of tsunami forecasting, to ensure that residents do not ignore evacuation warnings due to false impressions of the safety provided by seawalls.